2007
DOI: 10.1073/pnas.0700636104
|View full text |Cite|
|
Sign up to set email alerts
|

Primary cilia mediate mechanosensing in bone cells by a calcium-independent mechanism

Abstract: Primary cilia are sensory organelles that translate extracellular chemical and mechanical cues into cellular responses. Bone is an exquisitely mechanosensitive organ, and its homeostasis depends on the ability of bone cells to sense and respond to mechanical stimuli. One such stimulus is dynamic fluid flow, which triggers biochemical and transcriptional changes in bone cells by an unknown mechanism. Here we report that bone cells possess primary cilia that project from the cell surface and deflect during fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
406
2
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(444 citation statements)
references
References 61 publications
26
406
2
3
Order By: Relevance
“…7,9,29 Primary cilia are known to participate in a number of biological processes ranging from chemo-and mechanosensitivity to the transduction of paracrine signaling cascades that are critical for the development and maintenance of different tissues and organs. 30 These sensory organelles have been described in a variety of connective tissue cells [6][7][8][9][10][11] and have been implicated in the homeostasis of the skeleton. 16,8 It has been postulated that primary cilia projecting from cells into the extracellular matrix are exposed to fluid flow shear stress, mechanical deformation, and/or pressure gradients which, in turn, trigger a cellular response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,9,29 Primary cilia are known to participate in a number of biological processes ranging from chemo-and mechanosensitivity to the transduction of paracrine signaling cascades that are critical for the development and maintenance of different tissues and organs. 30 These sensory organelles have been described in a variety of connective tissue cells [6][7][8][9][10][11] and have been implicated in the homeostasis of the skeleton. 16,8 It has been postulated that primary cilia projecting from cells into the extracellular matrix are exposed to fluid flow shear stress, mechanical deformation, and/or pressure gradients which, in turn, trigger a cellular response.…”
Section: Discussionmentioning
confidence: 99%
“…30 These sensory organelles have been described in a variety of connective tissue cells [6][7][8][9][10][11] and have been implicated in the homeostasis of the skeleton. 16,8 It has been postulated that primary cilia projecting from cells into the extracellular matrix are exposed to fluid flow shear stress, mechanical deformation, and/or pressure gradients which, in turn, trigger a cellular response. 16 It has also been suggested that the magnitude and duration of these physical signals could lead to the remodeling of cilia structure through a change in its length via a feedback mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains to be determined if PKD1 and PKD2 function in a similar manner in both kidney and bone (86). Recently, Jacobs and colleagues have shown that primary cilia in bone cells do not mediate calcium flux in response to fluid flow, therefore the mechanism used by cilia in bone cells is distinct from that of kidney cells (76). Reducing the number of cilia reduces the induction of osteopontin in MC3T3 osteoblast cells, the induction of prostaglandin in both MC3T3 and MLOY4 osteocyte cells, and the increase of COX2 and OPG/RANKL ratio in MLOY4 cells in response to fluid flow shear stress.…”
Section: The Potential Role Of Cilia In Bone Cell Mechanotransductionmentioning
confidence: 99%
“…59 Malone et al 60 have recently demonstrated that fluid flow deflects the primary cilium in models of osteoblastic and osteocytic cells, and disruption of the cilium via pharmacological or genetic means diminishes the effects of fluid flow on prostaglandin production and osteopontin expression. However, disrupting the primary cilium did not affect the ability of osteoblastic cells to respond to fluid flow with an increase in intracellular calcium, as is the case in kidney cells, 61 suggesting that other mechanosensory mechanisms must work in conjunction with the cilium.…”
Section: Putative Mechanosensorsmentioning
confidence: 99%